Financial Vulnerability Among B40 Seniors in Malaysia - Fahd Al-shaghdari; Rusni Hassan; Syarah Syahira Mohd Yusoff; Syed Marwan Mujahid Syed Azman; Syed Salman; Nurul Afidah Mohamad Yusof (Universiti Sains Islam Malaysia, 2026)
The main purpose of this research is to identify novel contributing factors that increase vulnerability to financial risks of B40 seniors aged 60 or above in Malaysia and to identify the most critical factor affecting financial vulnerability among this group. The study utilises quantitative research method, using a convenience sampling method to collect data in the form of a survey design among 208 Malaysian B40 senior citizens. The collected data were analysed via SPSS Version 28. Through empirical analysis, it was ascertained that medical costs, saving habits, and support from the social environment are significant factors affecting the financial vulnerability of B40 Malaysian seniors. Yet the results found statistically insignificance relationship between financial literacy and financial vulnerability among B40 Malaysian seniors. These findings indicate that vulnerability among low-income seniors arises primarily from systemic inadequacies, particularly unaffordable healthcare, limited savings capacity, and weakening safety nets, rather than individual knowledge deficits. In response to these structural challenges, the study highlights the potential role of Islamic social finance in strengthening elderly financial resilience. Instruments such as subsidised takaful health schemes, waqf-based support funds, and targeted zakat assistance can alleviate medical burdens and reinforce social protection mechanisms. The findings therefore support the need for integrated, Shariah-aligned policy reforms to enhance financial security and promote inclusive ageing within Malaysia’s B40 community.